From east to west and back again: the effects of reverse culture shock on female Saudi Arabian university students studying abroad. Issue 2 (4th November 2021) - Winkel, Carmen; Strachan, Laura; Aamir, Siddiqua
Abstract : Purpose: The purpose of this study is to explore the experiences of Saudi Arabian university students returning home after having spent time away studying internationally. The investigation focused exclusively on female students who for diverse reasons were unable to complete their studies abroad. Design/methodology/approach: A thematic analysis was applied to analyze the seven in-depth interviews conducted by the authors. By using an open coding method analytic patterns across the entire data set were identified and then analyzed. Findings: The findings suggest that the students experienced reverse culture shock reintegrating and assimilating into their former lives in the Kingdom of Saudi Arabia and its conservative culture. This was especially surprising considering not one of the participants experienced culture shock when they first traveled to their host country – the USA, Canada or England. Research limitations/implications: The study is limited to a small group of seven female undergraduates who are comparatively well educated and come from a middle and upper socioeconomic demographic. As a result, without additional research, the findings cannot be extended to groups outside of this demographic. Practical implications: Students who have studied abroad need improved academic and social support networks when they return home, according to the findings. The authors want to raise awareness about the difficulties that students face upon their return. Teachers, counselors, and advisors need to be on the lookout for the symptomatology associated with these types of problems. Social implications: Female Saudi students returning home after an extended period of study abroad face a variety of problems. They must fit into a restrictive, partriarchal culture in which they are not legally equal to men. Originality/value: To date, there are no studies that shed light on reverse culture shock for students who returned to Saudi Arabia without a degree. Due to the large number of Saudi scholarship holders who study in English-speaking countries with government support, the study is the first attempt in this direction.